Experiences of Registered Nurses in Caring for Abused Elderly - Phoromyen, Suwaraporn; Kespichayawattana, Jiraporn (Journal of Health Science of Thailand, 2018)
This research was conducted with the objective of studying the experiences of registered nurses in caring for abused elderly. The methodology employed was phenomenology qualitative research. The subjects providing the majority of the data were ten registered nurses with experiences in caring for or assisting elderly patients who have been abused. The data was collected by in-depth interviews and recorded by tape. The data obtained was handled by verbatim transcription and the data analysis was undertaken by content analysis. The research findings on the experiences of registered nurses in the care for abused elderly included the following: 1. According to the perception of the registered nurses, abuse of the elderly meant actions that created sufferings and made the elderly feel worthless wherein their children and grandchildren were not appreciative of them. The events that occurred were the result of changes in emotions that could take place at any time. 2. The experiences of the registered nurses in caring for elderly who had been abused included three main topics or themes. a) No expectations of having this type of problem occur in Thai society resulting in feelings of despair, sorrow, pity and empathy for both sides once learned about the abuse. Furthermore, they held the opinion that staff overlooked the problem and were not conscientious about it. Moreover, it was still a problem stemming from economical problems and societal changes; b) Finding ways to solve the problem by knowing the details of the problem in depth and having skills in proper assessment; c) Finding problem-solving and assistance methods by being a mediator in generating understanding for the elderly and their families, including going in to solve the problems at the cause by giving the elderly encouragement, so they would be self-reliant, and trying to raise consciousness among younger generation and other family members.